HIV self-testing awareness among African refugee male sex workers in Italy: A mixed-methods study - Henry Delali Dakpui; Gamji Rabiu Abu-Ba’are; Mubarik Sena Saaka; Donte Boyd; Orlando Harris; Giovanni Zardini (PLoS ONE, 2026)
HIV disproportionately affects African refugee male sex workers (ARMSWs) in Italy, who face individual, structural and systemic barriers to HIV prevention and care services. HIV self-testing (HIVST) offers a promising strategy to improve testing access, yet awareness remains understudied in this population. This study examines HIVST awareness and associated factors among ARMSWs to inform targeted interventions. A mixed-methods sequential exploratory design was employed, combining quantitative surveys (n = 150) with qualitative interviews (20 in-depth interviews, 2 focus group discussions) among ARMSWs in Italy. Participants were recruited through venue-based and snowball sampling in partnership with a community organization. Quantitative data on HIVST awareness and correlates, including sociodemographic, healthcare access, and sex work characteristics, were analyzed using chi-square tests and logistic regression. Qualitative data from audio-recorded interviews underwent summative content analysis to explore awareness pathways and perceptions. Key findings revealed only 45% of participants were aware of HIVST, with just 47.8% of these having ever used a self-test. Higher education (aOR=1.92, p = 0.022) and prior STI testing (aOR=2.32, p = 0.015) significantly predicted awareness of HIVST. Qualitative data showed two awareness pathways: first-time exposure through the study and prior encounters via clients or community programs. Participants highlighted HIVST’s privacy and convenience as key benefits. Community-based, peer-led approaches, combined with healthcare provider engagement, are essential for increasing HIVST awareness and uptake among ARMSWs. These findings have broader implications for improving HIV testing strategies among hard-to-reach migrant populations across Europe.